Thickness Effect on Fluctuation of Electron States in Thin Film and Implications for Lattice Constant Change Due to Size Reduction - Nadya Amalia; Sparisoma Viridi; Mikrajuddin Abdullah (Journal of Mathematical and Fundamental Sciences, 2017)
We propose a model for predicting the fluctuation of electron states in thin films as a function of film thickness. The model is derived based on the assumption of the existence of potential barrier fluctuation on the film surface. Since the wave functions of electrons in the film are determined by the boundary conditions of the potential on the film surface, the potential fluctuation on the film surface implies fluctuation of the electron states in the film. The model was extended to predict the effect of size on the lattice constant of thin films or nanoparticles.